The estimation of NMVOC emissions from an urban-scale wastewater treatment plant - (:unkn) unknown (PERGAMON-ELSEVIER SCIENCE LTD, 2004)
The emissions of 19 different non-methane volatile organic compounds (NMVOCs) from the sewage treatment plant of the province of Eskisehir in Turkey were estimated. The estimations were based on the modified surface-renewal model suggested by EPA. The estimated total annual amounts of the pollutants emitted (from the plant's primary and secondary clarifier units and their weirs, as well as the aerated biological treatment unit) varied between a range of 0.00024t (1,3-dichlorobenzene) and 0.1646t (tetrachloroethylene). The corresponding flux data ranged from 9.98 x 10(-10) gcm(-2) h(-1) (1,3-dichlorobenzene) to 8450 x 10(-10) g cm(-2) h(-1) (tetrachloroethylene). Resulting total hourly NMVOC emission rate (0.041 kg h(-1)) was found not to exceed the current national standards. This work may be considered as a regional background for a possible contribution to the national and international emission inventory study on NMVOCs. (C) 2004 Elsevier Ltd. All rights reserved.
Keywords: volatile organic compounds; wastewater treatment plant; water-to-air mass transfer; volatilization; emission inventory; VOLATILE ORGANIC-COMPOUNDS; COMPOUNDS VOC; AIR; VOLATILIZATION; DISPERSION; ATMOSPHERE; DEPOSITION; INVENTORY; AERATION; GREECE